Design of Asymmetric Janus Aerogel Toward High-Performance Solar Evaporation - Luo, Liumin; Wang, Airong; Zheng, Luhan; Jia, Xiaxuan; Shi, Ge; Li, Yizhen; Peng, Jin; Shang, Mengya (Engineering Science & Technology, 2026)
Interfacial solar evaporation technology enables high-efficiency evaporation with low energy consumption through solar-driven localized heating and has broad application prospects in seawater desalination and industrial wastewater treatment. As novel functional materials with asymmetric physicochemical characteristics, Janus aerogels provide a new approach for overcoming the performance limitations of traditional evaporators. In this work, a Janus aerogel was fabricated using Polyvinyl Alcohol/Cellulose Nanofiber (PVA/CNF) as the substrate and Carbon Nanotubes (CNT) as the photothermal layer. Owing to its asymmetric structure, which integrates hydrophilic water transport and hydrophobic photothermal characteristics, the resulting aerogel achieves efficient photothermal conversion and directional water delivery. Its maximum surface temperature reaches 64.4 °C with a light absorption efficiency of 99%, consistent with the finite element simulation results. Under 1 sun, the evaporation rate is 1.32 kg·m-2·h-1 and the corresponding evaporation efficiency is 88.37%, and the aerogel maintains stable evaporation performance over 7 cycles, with only minor salt precipitation on the surface after 2 h of irradiation. This developed material shows promising potential in seawater desalination and wastewater purification, offering a novel strategy for the rational design of multifunctional aerogel evaporators.